Efecto de la liofilización sobre las propiedades funcionales del ají rocoto (Capsicum pubescens) (2017)
The chili pepper (Capsicum pubescens) is a perishable fruit whereby it is necessary to explore agroindustrial alternatives, that preserves its functional properties; within the technological developments studied in food processing and preservation is freeze-drying. In this research, the rocoto chili pepper harvested in rural area of San Cristobal-Medellin, Antioquia (Colombia), was freeze-drying and it was evaluated the effect on the functional properties such as antioxidant capacity by the Ferric Reducing Antioxidant Power method (FRAP), total phenols, carotenoids, ascorbic acid and capsaicin, both in the fresh product and in freeze-drying treatments. Was realized a fix split plots, with the factor of programming the heating rate, between 0.02 and 0.05°C/min during sublimation assigned to the principal plot and the categorical factor seeds in the subplot, was performed with a Randomized Block Design (RBD) with three replications. It was obtained in fresh chilli with seed including placenta values of 1.18mg of eq. ascorbic acid/g dried basis (d.b.) as antioxidant capacity by FRAP; 5.37mg of eq. gallic acid/g d.b. for total phenols content; 4.74mg/g d.b. of carotenoids; 1.88mg/g d.b. of ascorbic acid and 1.57mg/g d.b. of capsaicin. It was concluded that for the freeze-drying treatments, the antioxidant capacity and total phenols were increased, with respect to the fresh product. It evidenced a statistical difference in the heating schedules during sublimation affecting the capsaicin content in seed and seedless treatments.